ANDROID BASED DATA QUALITY CONTROL (QC) PROCESSING SYSTEM WITH FOUR AND TEN POINT SYSTEM GRADING METHOD IN PT MKP - Arifin, Ahmad Soleh; Tiowati, Sulis; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
Quality Control (QC) is the stage needed to assess the quality of the textile products produced, to determine the grade quality of a textile must be done a good calculation so that the grade results are in accordance with the standards applicable in the company. At the textile grade calculation company is still done in writing, so the calculation will often experience errors, this results in a lot of time wasted to do the calculation that is the average time required is two weeks of work hours. The company wants the calculation of textile grade determination can be done systematically, so that there is no error in determining the textile grade that will be distributed to the company's clients. The solution offered is to build an Android-based quality control system specifically to determine the grade results of textiles using the four point system grading method for evaluating textile quality (grade) for export and ten point grading system for local. The application of grading method in this system is to get the results of determining the grade of textile products more easily and faster in its calculations. The results of the design are in the form of a system that can carry out a quality control (QC) process to determine the grade of textiles using the four and ten point grading system method in textile production companies.